Interpelaciones identitarias en la Guerra del Chaco Boreal. Posicionamientos gubernamentales e intereses empresariales, 1932-1935 (Res Gesta, 2018)
The warlike conflict over the Chaco Boreal occurred in 1932 and 1935, between Bolivia and Paraguay, has left an indelible mark on the national histories of these countries. And, it acquired a degree of intensity, due to its international connotation, in the border territories of neutral nations such as Argentina. It is the purpose of this work to advance some ideas in the field of the current historiographical discussion on the subject and what it could represent in the political and cultural order of Salta. For this, it is intended to explain the development of certain “milestones” that are resignified in the discursive narratives, that intersect and overlap at different levels of analysis and come to constitute in contemporary sources the facts that are described and interpreted; as it is observed with the official publications and what was communicated through the graphic media of the time. A large number of these ideas comes from the study of the positioning regarding war by various political and social actors, as well as “from the margin”, may generate dissent and new quarrels around the constructions of historical discourse; at the same time to “cover”, in part, a gap in regional historiography
Keywords: Chaco War; Government Positioning; Oil Interest; Salta; Argentina